Prosedur dan Pengawasan Pemberian Kredit Untuk Mempertahankan Likuiditas Perusahaan Pada Koperasi Simpan Pinjam Rasa Mandiri Kota Batu Tahun 2020-2022 - Nur Ali; Mohammad Rizal; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Procedures for granting credit and credit monitoring are a thing which is closely related to reducing the occurrence of problem loans in a company. Therefore this study aims to determine the procedure and supervision of lending and strategies to maintain liquidity at “Rasa Mandiri” Cooperative.This type of research is descriptive qualitative. Done by conduct interviews with parties directly related to the Cooperative and analyze financial reports using liquidity ratios namely Cash ratio, Loan to Deposit Ratio (LDR), Loan to Asset Ratio (LAR) and Net Performing Loans (NPL).The results of this study indicate that procedures and supervision credit granting implemented by the Rasa Mandiri Cooperative can be said pretty good. The results of this study also indicate that the level of liquidity has not fully optimal, this is shown in the LDR ratio which decreases as a result distribution of credit is so large and the level of bad credit. This was due to the Covid 19 pandemic that hit the world at that time. But if seen of the NPL ratio which continues to decrease indicates that the procedure and supervision that is implemented properly and by the provisions of the can minimize the occurrence of errors when distributing credit.  Keywords: Procedures for Granting Credit, Supervision of Credit, and Liquidity